Ozonation Of Exhaust Gases. - Amri, Nurulhuda (2005)
Basically, exhaust gases for combustion process is containing gases such as NOx,CO, SO2 and other gases. The NOx gases is formed when nitrogen and oxygen atoms in the air react under the high pressure and temperature conditions in an engine. When NOx released to the atmosphere, it will cause the depletion of atmosphere ozone,O3.